DIGITALISASI MANAJEMEN KEARSIPAN DALAM PERSPEKTIF KEPEMIMPINAN PENDIDIKAN DI ERA TEKNOLOGI INFORMASI - Firdaus Pamungkas; Luzzah Azzahra; Ngaisyah Laila Agustin; Nijwa Aulia Rais; Siswadi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to analyze the digitalization of records management from the perspective of educational leadership in the era of information technology. Technological advancements require educational institutions to transform their archival management systems to become more effective, efficient, and systematic. Educational leadership plays a strategic role in directing policies, decision-making, and implementing digital archival systems in schools. This research employs a qualitative approach through literature review by examining various relevant scientific sources such as journals, books, and previous studies. The findings indicate that digital archival systems enhance accessibility, security, and efficiency in records management. Furthermore, adaptive, innovative, and visionary educational leadership is a key factor in the successful implementation of digital records management. Therefore, the synergy between technology and educational leadership is essential to achieve effective archival governance in the digital era. Keywords: digitalization, records management, educational leadership, information technology, archival effectiveness